ANALISIS DAMPAK KARAKTERISTIK DEMOGRAFI PADA PEROLEHAN PENDAPATAN PEKERJA PEREMPUAN SEKTOR INFORMAL DI KOTA PALEMBANG - Wulantari, Raden Ayu; Armansyah, Armansyah (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2018)
This study aims to explain the impact of demographic characteristics on the income earning of informal sector workers in Palembang City. The method used mixed methode, which is a combination of quantitative and qualitative. Data collection by observation, interview and documentation. Data obtained from the informant selected by purposive sampling. Collected quantitative data were analyzed using the SPSS Program through the analysis of frequency decryption and crosstabs, while the qualitative analysis used the steps of reduction, display, and conclution. The validity of data uses degree of credibility with techniques of persistence enhancement, extension of observation, triangulation, and member checking. The results showed that demographic characteristics such as; age, status, education, skills and occupation have an impact on the earnings of informal sector women's incomes whereas training has no impact on the earnings of informal sector workers